2017
DOI: 10.4041/kjod.2017.47.2.87
|View full text |Cite
|
Sign up to set email alerts
|

A three-dimensional photogrammetric analysis of the facial esthetics of the Miss Korea pageant contestants

Abstract: ObjectiveThe aims of this study were to measure and compare the facial dimensions of the Miss Korea pageant contestants and a selected group of women from the general population by using three-dimensional (3D) image analysis, as well as to compare various facial ratios to the golden ratio within each group.MethodsThree-dimensional images of 52 Miss Korea pageant contestants (MK group) and 41 young female adults selected from the general population (GP group) were acquired. Fifty-four variables and ratios were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 36 publications
2
25
1
1
Order By: Relevance
“…At present, increasing numbers of patients are seeking orthodontic treatment to improve facial attractiveness, which improves their quality of life. [17,18] Especially lip position, cheek volume, and chin contour play an important role with facial profiles. [19,20] In this case report, the patient had prominent lips and chin with a broad zygomatic process and slightly concave profile which is considered less attractive.…”
Section: Discussionmentioning
confidence: 99%
“…At present, increasing numbers of patients are seeking orthodontic treatment to improve facial attractiveness, which improves their quality of life. [17,18] Especially lip position, cheek volume, and chin contour play an important role with facial profiles. [19,20] In this case report, the patient had prominent lips and chin with a broad zygomatic process and slightly concave profile which is considered less attractive.…”
Section: Discussionmentioning
confidence: 99%
“…The proportions from portraits are closer to ‘ideal’ than in ratios measured clinically. Jang et al undertook measurements from three-dimensional sampling of 93 patients in a Korean population and concluded that a longer face, smaller lip and chin size were preferable in females of a Korean population and this is a deviation from the golden ratio [ 61 ]. Milutinovic et al assess different facial proportions and their relationship to attractiveness in Caucasians and any deviations from the ideal proportions or the divine ratio.…”
Section: Discussionmentioning
confidence: 99%
“…Taking advantage of 3D facial imaging technology, Moss et al observed complex patterns of facial changes with treatment among adolescent orthodontic patients (7). In awareness of the complexity of facial structures, Kab et al divided 3D facial surface into multiple regions for separate analysis (8).…”
Section: Introductionmentioning
confidence: 99%